Developing a two-prong cognitive diagnostic assessment model (CDAM) for rimary mathematics learning. - Chew , Cheng Meng

(untitled)
With the latest shift to school-based assessment [SBA), school teachers are assigned a bigger role in designing appropriate assessments and making decision about pupils' learning. However, anecdotal evidence from teachers complementing the new curriculum suggested that these teachers need more support, particularly in mastering school based assessment, active learning pedagogy and the promotion of higher-order thinking skills.